2009
DOI: 10.1111/j.1365-2893.2008.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association between hepatic stellate cell apoptosis and fibrosis in chronic hepatitis C virus infection

Abstract: Perisinusoidal hepatic stellate cells (HSC) are the principal fibrogenic cells in the liver. In animal models, HSC apoptosis is the predominant clearance mechanism of activated HSC, although data evaluating whether the same processes occur in humans are limited. We conducted a cross-sectional study to evaluate the association between HSC apoptosis and fibrosis stage in subjects with chronic hepatitis C virus (HCV) infection (n = 44) and HCV-negative controls with normal liver histology (n = 9). We used immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Additionally, genes known to be expressed by activated HSCs, such as Bcl-2 associated X (BAX), which are also related to chemoattraction and apoptotic induction were upregulated. This contrasts with the downregulation of genes associated with inhibition of apoptosis (such as baculovirus IAP repeat-containing 5 [BIRC5]) and cell cycle progression (such as p21-activated kinase 7 [PAK7] and kinesin family member 11 [KIF11] and is consistent with a report that HSC apoptosis is anticorrelated with HCV-induced fibrogenesis (Gonzalez et al, 2009a). Taken together, these findings suggest that in HCV/HIV coinfected patients, increased migration of activated immune effector cells likely contributes to increased hepatic inflammation.…”
Section: Resultssupporting
confidence: 88%
“…Additionally, genes known to be expressed by activated HSCs, such as Bcl-2 associated X (BAX), which are also related to chemoattraction and apoptotic induction were upregulated. This contrasts with the downregulation of genes associated with inhibition of apoptosis (such as baculovirus IAP repeat-containing 5 [BIRC5]) and cell cycle progression (such as p21-activated kinase 7 [PAK7] and kinesin family member 11 [KIF11] and is consistent with a report that HSC apoptosis is anticorrelated with HCV-induced fibrogenesis (Gonzalez et al, 2009a). Taken together, these findings suggest that in HCV/HIV coinfected patients, increased migration of activated immune effector cells likely contributes to increased hepatic inflammation.…”
Section: Resultssupporting
confidence: 88%
“…In addition, we found colocalization of a-SMA (marker for activated HSCs) and active caspase-3 (marker for apoptosis) in the liver biopsy specimens from HCV-positive patients, indicating that HSC apoptosis indeed occurs in HCV( þ ) livers. Accordingly, Gonzalez et al 26 recently demonstrated intra-hepatic HSC apoptosis to be inversely correlated with the stage of fibrosis in chronic HCV. Finally, we observed an inverse correlation between NK cell-induced HSC apoptosis and the stage of liver fibrosis, with significantly higher anti-HSC activity of NK cells in patients without fibrosis than in patient with F1/F2 and F3/F4 fibrosis, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the removal of activated HSCs is the primary hepatic fibrosis treatment strategy. Many recent studies have focused on the apoptosis of activated HSCs, indicating that this apoptosis mainly contributes to the reversal of hepatic fibrosis [4], [5]. Therefore, the induction of apoptosis in activated HSCs may be an effective hepatic fibrosis treatment strategy.…”
Section: Introductionmentioning
confidence: 99%